Rancangan Fasilitas Tempat Penampungan Sampah di Jalan Pangeran Ratu B Kota Palembang - Sandy, Listia Monica; ., Firdaus; Mulyati, Ely (Jurnal Sains dan Teknologi (JSIT), 2026)
Population growth and urban activities in Palembang City have led to an increase in waste generation, particularly in the Jalan Pangeran Ratu B area, which has a high density of residential and commercial activities. The existing conditions show limitations in the capacity of temporary storage sites (TPS), designs that are not environmentally friendly, and low implementation of waste sorting at the source. This study aims to design a TPS facility that meets waste generation capacity needs, complies with technical standards, and supports sustainable waste management. The research methods include field observations, primary and secondary data collection, waste generation analysis using the formula Q = P × q, and TPS technical design. The analysis results show that the volume of waste generation in 2025 will reach 64.74 m³/day with an average growth rate of 13.4% per year and is projected to increase to 121.42 m³/day in 2030. The planned TPS is categorized as a Type II TPS with a capacity of 15–20 m³, equipped with a sorting area, drainage system, natural ventilation, and supporting facilities based on the 3R concept. This design is expected to improve the effectiveness of waste management, reduce environmental impact, and support the creation of a clean and sustainable urban environment.